The conservation of a gender fantasy: women and Top 40 radio in Montreal - Maki, Christine (Université McGill, 2008)
This work examines today's Anglophone Top 40 radio in Montreal in terms of gender. Looking at the history of commercial radio, and the historical relationship between radio and women, it argues that these radio stations have always programmed based on an imagined rather than actual understanding of their target audience. Programmers today continue to hold a conservative understanding of their female audience and their interests, and to program using a stereotypical understanding of gender.